Perancangan Interior Café untuk Meningkatkan Interaksi Sosial di Surabaya - Evelyn Budi Santoso; Sherly de Yong; David Tan Kayogi (Intra, 2019)
The Increasing usage of gadget have an impact on decreasing interaction level between humans. The definition of café according to Building Planning & Design is a space that can be used as a place to relax dan chat. Basically, according to the definition, café is suitable for accommodating human activities to build social interaction. However, in reality when people gather at the café, people will tend to have lack communication with each other and get busy with their own gadgets. The purpose of the interior design is to build social interaction for the visitors. The design method used was Design Thinking which consist of understanding, observe, point of view, ideate, prototype, test, and implementation. The design result is Play Day Social Café designed with the concept of Oodles of Fun, which will give the impression of fun, mood booster, enjoyable, catchy, and flexible about this café, and providing facilities like board game  and books like novels and comics which often loved by teenager/young adult on range 15-25 years old to, directly or not, present social interaction.